Guest room. - Janowicz, Marianna (Architectural Review, 2024)
The article from Architectural Review discusses the concept of a guest room as a space for unexpected visitors or temporary residents, such as out-of-town family members or friends in need. The author emphasizes the importance of a welcoming and flexible design that can accommodate various needs and situations. The example of La Borda, a co-operative housing scheme in Barcelona, is used to illustrate how shared facilities, including guest rooms, can provide a sense of community and support.